A method for characterizing rock acid erosion damage strength in acid fracturing
Patent Information
- Application Number
- CN202611107655.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明的目的在于提供一种酸化压裂中岩石酸蚀损伤强度的表征方法,该方法具备酸蚀形貌平整修复、分层深度剖面制备、微观力学参数定量测试、表征损伤强度演化规律的功能,解决了现有技术无法精准并定量表征岩石酸蚀强度损伤的关键技术问题
[0029]与现有技术相比,本发明的有益效果为:本发明通过环氧树脂真空负压充填固化的方式,将酸蚀后凹凸不平的粗糙表面修复为平整的岩-胶复合界面,从根本上解决了微纳米压痕技术无法在酸蚀粗糙表面开展有效测试的行业难题,排除了表面几何形貌对力学测试结果的干扰,能够直接测得岩石基质本身的真实微观力学损伤,测试数据稳定性与准确性显著提升。同时采用逐层打磨抛光的分层剥离方案,可获得酸蚀损伤强度随深度的连续变化剖面,结合指数衰减模型能够定量拟合损伤演化规律,明确酸蚀损伤的有效影响深度,弥补了传统宏观测试仅能获得整体综合强度、无法揭示损伤深度分布规律的缺陷。相较于仅能定性观测微观结构的扫描电镜、X射线衍射等手段,本方法可定量表征的微观硬度、弹性模量等力学参数,实现了酸蚀损伤的精准量化评价。该方法适配碳酸盐岩、致密砂岩等多种储层岩石类型,可模拟不同酸液体系与温压工况,能够为酸化压裂工艺优化、酸蚀裂缝长期稳定性评价及储层伤害评估提供可靠的力学依据。
Smart Images

Figure CN122921907A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of reservoir stimulation technology in oil and gas field development, and in particular to a method for characterizing the intensity of rock acid erosion damage during acid fracturing. Background Technology
[0002] Acid fracturing is one of the core technologies for enhancing the production of carbonate and tight sandstone reservoirs. Its principle involves injecting acid into the formation under high pressure. The acid reacts heterogeneously with the rock minerals, creating etched pores and fractures on the surface. These etched features, upon stress closure, can form acid-etched fractures with high conductivity, which is crucial for successful fracturing. However, while dissolving minerals, the acid also causes irreversible micromechanical damage to the rock's framework, including weakening mineral grain boundaries, generating microcracks, and reducing the overall strength of the rock. This acid-induced mechanical damage directly affects the stability of fractures during long-term production, potentially leading to increased proppant embedding, fracture closure, or even failure.
[0003] Currently, the main method for evaluating the impact of acid etching on rock mechanics is a macroscopic mechanical comparison test before and after acid etching, such as uniaxial / triaxial compression tests or Brazilian splitting tests. These methods have significant drawbacks: the rock surface after acid etching is extremely uneven, resulting in highly uneven stress distribution and large dispersion in the test results when directly performing macroscopic mechanical tests. Furthermore, these methods reflect the overall strength of the rock, including the influence of geometric morphology, and cannot isolate purely mechanical damage. Another method is to observe microstructural changes using scanning electron microscopy (SEM) or X-ray diffraction (XRD), but this can only provide a qualitative description and cannot obtain quantitative mechanical parameters. While micro / nano indentation technology can test the mechanical properties of micro-areas, testing directly on the uneven surface after acid etching leads to unstable indenter contact points, making it impossible to effectively obtain changes in the microscopic mechanical parameters of the rock matrix after acid etching. Summary of the Invention
[0004] The purpose of this invention is to provide a method for characterizing the intensity of acid erosion damage in rocks during acid fracturing. This method has the functions of smoothing and repairing the acid erosion morphology, preparing layered depth profiles, quantitatively testing micromechanical parameters, and characterizing the evolution law of damage intensity. It solves the key technical problem that existing technologies cannot accurately and quantitatively characterize the intensity of acid erosion damage in rocks.
[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:
[0006] A method for characterizing the intensity of rock acid etching damage during acid fracturing includes the following steps:
[0007] Step S1, Sample preparation: The target rock is processed into a cylindrical rock sample, with only one end face exposed as the surface to be acid etched. All other surfaces of the rock sample are covered with an acid-resistant protective layer to achieve directional single-sided acid etching.
[0008] Step S2, acid etching treatment: Place the coated rock sample in a reaction container so that the exposed end face comes into contact with the acid solution and carry out the acid etching reaction under the preset reservoir conditions.
[0009] Step S3, Filling and Curing: Clean and dry the acid-etched rock sample, and use epoxy resin to fill the acid-etched end face with vacuum negative pressure, so that the epoxy resin completely fills the acid-etched pores and microcracks, and after curing, a smooth rock-resin composite end face is formed.
[0010] Step S4, Profile Preparation: Using the filled composite end face as a reference, the rock sample end face is polished layer by layer. After each polishing to a preset depth, polishing is performed to obtain a smooth test surface at different acid etching depths.
[0011] Step S5, Micromechanical Testing: Micro-nano indentation technology is used to test the flat test surface at each depth to obtain the micromechanical parameters of the rock matrix at the corresponding depth.
[0012] Step S6, Damage Intensity Characterization: Using the micromechanical parameters of the undamaged rock matrix as the benchmark, calculate the difference between the test value and the benchmark value at different acid etching depths to obtain the acid etching damage intensity at the corresponding depth, and establish a quantitative evolution relationship between the evolution of acid etching damage intensity and acid etching depth.
[0013] Furthermore, in step S1, the rock sample is cylindrical, with only one end face exposed as the surface to be acid-etched, while the remaining surfaces, including the other bottom and side surfaces, are coated with an acid-resistant material to form a protective layer; the acid-resistant protective layer is a polytetrafluoroethylene acid-resistant coating or an epoxy resin-based acid-resistant adhesive, with an acid resistance temperature of not less than 150℃, an acid resistance pressure of not less than 10MPa, and a protective layer thickness of 0.4-0.6mm.
[0014] Furthermore, in step S2, the reaction vessel is a high-temperature and high-pressure reactor, and the reservoir operating conditions include acid concentration, reaction temperature, reaction pressure, reaction time, and pH value; during the reaction, the acid concentration is monitored in real time and acid is replenished, while stirring is carried out to ensure uniform acid concentration; the parameters are controlled through the reaction vessel to simulate different reservoir conditions.
[0015] Further, in step S3, the acid-etched rock sample is rinsed with flowing deionized water and dried at 40-50℃. The vacuum negative pressure filling process involves first injecting epoxy resin to submerge the acid-etched end face, then immediately placing it in a sealed chamber and evacuating it to -0.05-0.1MPa while maintaining pressure to expel gas from the pores and ensure that the epoxy resin penetrates the acid-etched pores and microcracks. Then, ultrasonic vibration is used for 5-10 minutes to remove air bubbles, followed by heat and pressure maintenance for 24 hours to complete the curing.
[0016] Furthermore, in step S4, the depth interval of the layer-by-layer grinding is 10μm-30μm, and the grinding depth covers the entire acid-etched layer to the undamaged bedrock layer; through step-by-step grinding and polishing, the surface roughness Ra is greater than 1000 mesh, so that it is Ra < 0.05μm.
[0017] Furthermore, in step S5, the micro-nano indentation test uses a Berkovich diamond indenter with a loading load range of 0.1-500mN and an indentation depth range of 100-5000nm; at least 49 test points are arranged in a matrix on each test surface, and the test points are placed in the rock matrix area to avoid the epoxy resin filled area.
[0018] Further, in step S4, the acid etching intensity loss value is calculated using the following formula:
[0019] ;
[0020] in, For depth The acid etching intensity loss value at the location; The baseline values for the micromechanical parameters of the undamaged rock matrix; For depth Test values of micromechanical parameters of rock matrix after acid etching.
[0021] Furthermore, in step S5, if the indentation points cover the bonding area between the epoxy resin and the rock, the bearing area ratio of the rock and epoxy resin is calculated through microscopic observation. The mechanical parameters obtained from the test are then corrected by area weighting using the following formula. After separating the microscopic mechanical parameters of the pure rock matrix, the acid etching strength loss value is calculated:
[0022] ;
[0023] in, These are the micromechanical parameters of the rock matrix; These are the comprehensive mechanical parameters obtained from the indentation test; This represents the percentage of the epoxy resin bearing area within the indentation range; These are the micromechanical parameters of pure epoxy resin;
[0024] The percentage of the bearing area of the rock matrix within the indentation range.
[0025] Furthermore, in step S6, the baseline value of the undamaged rock matrix is taken from the test results of the un-acid-etched area of the same rock sample, or from the test results of the rock sample being ground to the deep undamaged layer; the micromechanical parameters include microhardness and / or elastic modulus.
[0026] Furthermore, in step S6, an exponential decay model is used to fit the relationship between acid etching depth and acid etching damage intensity. The resulting evolution law of acid etching intensity loss value satisfies the following equation:
[0027] ;
[0028] in, This represents the loss of acid etching strength. This refers to the depth of acid etching. , , represents the fitting constant under the corresponding experimental conditions.
[0029] Compared with existing technologies, the advantages of this invention are as follows: This invention uses epoxy resin vacuum negative pressure filling and curing to repair the uneven and rough surface after acid etching into a smooth rock-colloid composite interface. This fundamentally solves the industry problem that micro-nano indentation technology cannot effectively test on acid-etched rough surfaces, eliminates the interference of surface geometry on mechanical test results, and can directly measure the true microscopic mechanical damage of the rock matrix itself, significantly improving the stability and accuracy of test data. Simultaneously, by employing a layer-by-layer grinding and polishing peeling scheme, a continuous profile of acid etching damage intensity changing with depth can be obtained. Combined with an exponential decay model, the damage evolution law can be quantitatively fitted, clarifying the effective depth of influence of acid etching damage, thus overcoming the shortcomings of traditional macroscopic tests that can only obtain overall comprehensive strength but cannot reveal the distribution law of damage depth. Compared with scanning electron microscopy and X-ray diffraction, which can only qualitatively observe microstructure, this method can quantitatively characterize mechanical parameters such as microscopic hardness and elastic modulus, achieving precise quantitative evaluation of acid etching damage. This method is applicable to various reservoir rock types such as carbonate rocks and tight sandstones, and can simulate different acid fluid systems and temperature and pressure conditions. It can provide reliable mechanical basis for optimizing acid fracturing processes, evaluating the long-term stability of acid-etched fractures, and assessing reservoir damage. Attached Figure Description
[0030] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof.
[0031] Figure 1 This is a schematic diagram of the layer-by-layer polishing and micro / nano indentation test point location structure according to an embodiment of the present invention.
[0032] Figure 2 This is a schematic diagram of the end face structure of the sample after epoxy resin filling and curing according to an embodiment of the present invention.
[0033] Figure 3 This is a schematic diagram of the sample preparation and acid etching process in an embodiment of the present invention.
[0034] The attached figures are labeled as follows: 1. Acid-etched pores; 2. Rock matrix; 3. Rock sample; 4. Epoxy resin; 5. Micro-nano indentation test. Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0036] It should be noted that all directional indications (such as up, down, left, right, front, back, etc.) in the embodiments of the present invention are only used to explain the relative positional relationship and movement of each component in a certain specific posture (as shown in the figure). If the specific posture changes, the directional indication will also change accordingly.
[0037] Furthermore, in this invention, descriptions involving "first," "second," etc., are for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0038] Please see Figure 1 , Figure 2 as well as Figure 3 , Figure 1 A schematic diagram of the layer-by-layer polishing and micro / nano indentation test point location structure provided for embodiments of this application. Figure 2 A schematic diagram of the end face structure of the epoxy resin-filled and cured sample provided in the embodiments of this application. Figure 3 This is a schematic diagram of the sample preparation and acid etching process provided for embodiments of this application. Embodiments of this application provide a method for characterizing the acid etching damage intensity of rocks during acid fracturing, specifically including the following steps:
[0039] Step S1, Sample Preparation: The target rock is processed into a cylindrical rock sample, with only one end face exposed as the surface to be etched by acid. All other surfaces of the rock sample are coated with an acid-resistant protective layer to achieve directional, single-sided acid etching. Specifically, in step S1, rock sample 3 is a cylinder with only one end face exposed as the surface to be etched by acid. The remaining surfaces, including the bottom and side faces, are coated with an acid-resistant material to form a protective layer. The acid-resistant protective layer is a polytetrafluoroethylene (PTFE) acid-resistant coating or an epoxy resin-based acid-resistant adhesive, with an acid resistance temperature of not less than 150℃, an acid resistance pressure of not less than 10MPa, and a protective layer thickness of 0.4-0.6mm.
[0040] Specifically, a full-diameter core sample from the target reservoir is taken and machined into cylindrical specimens with a diameter of 50 mm and a length of 25 mm using a drilling machine and a cutting machine. One end face of each specimen (referred to as the upper end face) is left naturally or lightly sanded smooth as the surface to be acid-etched. The other end face (lower end face) and the entire side of the cylinder are roughened with sandpaper to facilitate adhesive adhesion. An acid-resistant resin adhesive (bisphenol A type epoxy resin and phenolic amine curing agent) is prepared and evenly coated onto the lower end face and the entire side, forming a protective layer approximately 0.5 mm thick. The mixture is cured at room temperature for 24 hours, ensuring the upper end face is clean and free of adhesive.
[0041] By exposing one side and covering the rest with acid-resistant coating, the area affected by the acid etching reaction is strictly limited, preventing acid from penetrating the rock from the side or bottom and causing non-target damage. This ensures that the damage characterization in the subsequent depth direction has a clear reference surface and a unified boundary, effectively improving the accuracy and repeatability of the test results.
[0042] Step S2, Acid Etching Treatment: The coated rock sample is placed in a reaction vessel, allowing the exposed end face to contact the acid solution. The acid etching reaction is then carried out under preset reservoir conditions. The reaction vessel is a high-temperature, high-pressure reactor. The reservoir conditions include acid concentration, reaction temperature, reaction pressure, reaction time, and pH value. During the reaction, the acid concentration is monitored in real time and replenished, while stirring is performed to ensure uniform acid concentration. The parameters are controlled through the reaction vessel to simulate different reservoir conditions.
[0043] Specifically, the prepared sample is placed in a high-temperature, high-pressure reactor with its upper surface facing upwards. An acid solution is injected into the reactor, ensuring the liquid level completely submerges the upper surface but is below the upper edge of the protective layer. Reaction conditions are set as follows: temperature 90℃, pressure 5MPa, and reaction times of 0.5h, 1h, 2h, 4h, and 8h (two parallel samples at each time point). The acid concentration is monitored in real time; if the concentration is low, it is automatically replenished. A stirring device is used to continuously agitate the solution to ensure a uniform acid concentration distribution. After the reaction is complete, the pressure is released, and the sample is removed.
[0044] The use of a high-temperature and high-pressure reactor allows for precise control of temperature, pressure, and acid parameters, realistically simulating the actual acid etching conditions of underground reservoirs and ensuring that experimental results correspond to on-site conditions. The design of real-time acid replenishment and uniform stirring during the reaction process avoids the problem of acid concentration gradually decreasing as the reaction proceeds, ensuring uniform acid etching in all areas of the end face and reducing data dispersion between parallel samples.
[0045] Step S3, Filling and Curing: The acid-etched rock sample is cleaned and dried. Epoxy resin is then used to fill the acid-etched end face under vacuum negative pressure, ensuring the epoxy resin completely fills the acid-etched pores and microcracks. After curing, a smooth rock-resin composite end face is formed. The acid-etched rock sample is first rinsed with flowing deionized water and then dried at 40-50℃. The vacuum negative pressure filling process involves first injecting epoxy resin to submerge the acid-etched end face, then immediately placing it in a sealed chamber and evacuating it to -0.05 to -0.1 MPa, maintaining the pressure to expel gas from the pores and ensure the epoxy resin penetrates the acid-etched pores and microcracks. Then, ultrasonic vibration is applied for 5-10 minutes to remove air bubbles, followed by 24 hours of temperature control to complete curing.
[0046] Specifically, the acid-etched sample was rinsed in flowing deionized water for 30 minutes, followed by ultrasonic cleaning for 10 minutes to remove residual acid and reaction products. It was then dried in a 60°C oven for 12 hours. A low-viscosity epoxy resin (E51 epoxy resin, methylhexahydrophthalic anhydride curing agent, and accelerator DMP-30) was prepared. The sample, with the etched end facing upwards, was placed in a sealed chamber. Epoxy resin was injected until the end face was submerged. While the epoxy resin was still fluid, a vacuum was immediately drawn to -0.05 to -0.1 MPa and maintained to allow the fluid epoxy resin to penetrate the acid-etched pores and microcracks. An ultrasonic vibration table was then turned on for 10 minutes to completely remove air bubbles. Finally, the sample was kept at this temperature for 24 hours to allow the epoxy resin to fully cure.
[0047] By using low-viscosity epoxy resin for vacuum negative pressure filling, the rough and uneven damaged surface after acid etching is repaired into a smooth rock-resin composite interface, solving the industry problem that micro-nano indentation technology cannot be effectively tested on acid-etched rough surfaces. The combined process of vacuum extraction, pressure impregnation and ultrasonic debubbling ensures that the epoxy resin fully penetrates into micron- or even nano-scale microcracks and pores without any residual bubbles. The composite end face structure formed after curing is stable, providing uniform and stable contact conditions for subsequent micro-nano indentation testing, and completely eliminating the interference of surface geometry on the micromechanical test results.
[0048] Step S4, Profile Preparation: Using the filled composite end face as a reference, the rock sample end face is ground layer by layer. After each layer is ground to a preset depth, polishing is performed to obtain a smooth test surface at different acid etching depths. The depth interval of each layer of grinding is 10μm-30μm, and the total grinding depth covers the entire acid-affected layer to the undamaged bedrock layer. The surface roughness Ra is Ra < 0.05μm through progressive grinding and polishing at 100 mesh, 200 mesh, 300 mesh, 500 mesh to 1000 mesh, with each polishing being greater than 1000 mesh.
[0049] Specifically, the cured sample was fixed on an automatic grinding and polishing machine. Using the original acid-etched surface (i.e., the highest point after filling) as the reference zero point, the initial grinding depth was set to 0 μm. First, the end face was coarsely ground to remove excess epoxy resin. Then, it was finely ground sequentially using 100-grit, 200-grit, 300-grit, 500-grit, and 1000-grit sandpaper. Finally, it was polished with alumina polishing liquid until the surface roughness Ra < 0.05 μm, achieving a finish of 1000 grit or higher. This completed the preparation of the first test plane (depth 0 μm).
[0050] In some examples, the grinding depth interval can be set to 20 μm. The sample surface is then ground down to 20 μm, 40 μm, 60 μm, etc. After each depth is completed, the above polishing process is repeated to obtain a flat test surface at that depth.
[0051] By employing a layer-by-layer grinding and polishing process with equal depth intervals, a smooth test profile can be obtained at different depths within the acid etching influence range. This enables continuous layered characterization of acid etching damage from the surface to the interior, overcoming the limitation of traditional methods that can only test the overall average strength. High-precision polishing with a mesh size of 1000 or higher ensures that the surface roughness requirements of micro-nano indentation are met for each depth test surface, ensuring consistent test conditions at each depth and making the test results comparable laterally.
[0052] Step S5, Micromechanical Testing: Micro-nano indentation technology is used to test the flat test surfaces at various depths to obtain the micromechanical parameters of the rock matrix at the corresponding depths. The micro-nano indentation test uses a Berkovich diamond indenter with a loading range of 0.1-500 mN and an indentation depth range of 100-5000 nm. At least 49 test points are arranged in a matrix on each test surface. The test points are placed in the rock matrix region 2, avoiding the epoxy resin-filled area, meaning the test points are located in the rock matrix area as much as possible.
[0053] Specifically, a NanoIndenter G200 micro / nano indenter with a Berkovich diamond indenter was used. Test parameters were set as follows: maximum load 50 mN, loading rate 10 mN / s, hold time 10 s, and unloading rate 10 mN / s. On each test plane (depths 0, 20, 40, ...), a 7x7 matrix of test points was selected (avoiding obvious resin-filled areas; the indenter should land on the rock matrix) for indentation testing. The hardness (H) and elastic modulus (E) of each point were recorded. The mean and standard deviation of the 49 points at each depth were calculated.
[0054] The matrix-style multi-point testing method can effectively reduce the testing error caused by the heterogeneity of the rock and obtain statistically representative micromechanical parameters. The test points actively avoid the resin-filled area and select only the rock matrix area, which can directly measure the true mechanical properties of the rock matrix itself, eliminate the interference of the filling resin, and ensure that the test data directly reflects the degree of mechanical damage to the rock matrix caused by acid etching.
[0055] Step S6, Damage Intensity Characterization: Using the micromechanical parameters of the undamaged rock matrix as the benchmark, calculate the difference between the test values and the benchmark values at different acid etching depths to obtain the acid etching damage intensity at the corresponding depth, and establish a quantitative relationship between the evolution of acid etching damage intensity and acid etching depth.
[0056] (1) Formula for calculating acid etching intensity loss;
[0057]
[0058] in, For depth The acid etching intensity loss value at the location; The baseline values for the micromechanical parameters of the undamaged rock matrix; For depth Test values of micromechanical parameters of rock matrix after acid etching.
[0059] Using the original strength of the undamaged rock matrix as a benchmark, the magnitude of strength loss caused by acid etching is directly quantified by the difference. The definition is clear and the calculation is intuitive. It can directly reflect the degree of acid etching damage to the rock matrix at different depths, and realizes a breakthrough from qualitative description to quantitative characterization of acid etching damage.
[0060] (2) Determination of benchmark values and specification of parameters;
[0061] The baseline values for the undamaged rock matrix are obtained from the test results of the un-acid-etched area of the same rock sample, or from the test results of the rock sample ground to the deep undamaged layer, or can be obtained by testing the un-acid-etched end face (after grinding) of the same sample; the micromechanical parameters include microhardness and / or elastic modulus.
[0062] The role of epoxy resin is to fill the acid-etched pores and provide a smooth test surface. Its properties are constant and uniform, ensuring consistent indenter contact conditions during testing. It is not used as a basis for damage calculation. Pure epoxy resin blocks can be prepared separately, and their mechanical parameters can be calibrated using the same micro / nano indentation test parameters as in step S5, such as measuring the microhardness of the epoxy resin. =0.25GPa (this is an example value, the actual value shall be subject to testing), the standard deviation of the test results at different locations is less than 0.01GPa, and it has high uniformity.
[0063] Microscopic hardness of un-acid-etched primitive carbonate rocks It is usually in the range of 1.2-1.5 GPa.
[0064] The benchmark value is taken from the undamaged area of the same rock sample, which can eliminate the natural heterogeneity differences between different rock samples, ensure the uniformity of the benchmark for damage calculation, and greatly improve the accuracy of test results. The auxiliary role and calibration method of epoxy resin are clearly defined, which not only utilizes its uniform and stable characteristics to ensure consistent test conditions, but also avoids mixing the resin properties into the calculation of rock damage, thus ensuring the objectivity of damage characterization.
[0065] (3) Correction method for test data of rock-colloidal bonded area;
[0066] If the indentation points cover the bonding area between the epoxy resin and the rock, the ratio of the bearing area of the rock to the epoxy resin is calculated by scanning electron microscopy. The mechanical parameters obtained from the test are then corrected by area weighting. After separating the microscopic mechanical parameters of the rock matrix, they are substituted into the core formula to calculate the acid etching strength loss value. The correction formula is as follows:
[0067]
[0068] in, These are the micromechanical parameters of the rock matrix; These are the comprehensive mechanical parameters obtained from the indentation test; This represents the percentage of the epoxy resin bearing area within the indentation range; These are the micromechanical parameters of pure epoxy resin;
[0069] This represents the percentage of the rock matrix within the indentation area that bears the load.
[0070] Example: If 82% of the area of an indentation point is located within the epoxy resin and 18% is located on the rock matrix, substituting these areas into the corrected formula will allow us to separate the mechanical parameters of the pure rock matrix corresponding to that point. Details are as follows:
[0071]
[0072] in, For depth The intensity of acid etching damage at the site; The baseline values for the micromechanical parameters of the undamaged rock matrix; These are the comprehensive mechanical parameters obtained from the test of this indentation point; These are the micromechanical parameters of pure epoxy resin.
[0073] The example formula and the general correction formula: The derivation logic is completely consistent, except that the area percentage values of 82% and 18% are directly substituted in, and the formula for calculating the final damage intensity is written in one step.
[0074] For highly heterogeneous rocks such as sandstone, this correction method can effectively solve the problem of test data distortion caused by cross-contamination of indentation points between overlying rock and gel phases. By separating the true mechanical parameters of the pure rock matrix through area weighting, the utilization rate and accuracy of test data are greatly improved, and the adaptability to different types of rocks is expanded. It is especially suitable for tight sandstone reservoirs with well-developed pores and strong heterogeneity.
[0075] Finally, a curve was plotted with acid etching depth as the x-axis and damage intensity as the y-axis. An exponential decay model was used to fit the curve and obtain the evolution law of acid etching damage intensity. This can quantitatively determine the maximum deterioration range and effective influence depth of acid etching damage, providing a precise mechanical basis for optimizing acid fracturing process and evaluating the long-term stability of fractures.
[0076] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for characterizing the intensity of rock acid etching damage during acid fracturing, characterized in that, Includes the following steps: Step S1, Sample preparation: The target rock is processed into a cylindrical rock sample, with only one end face exposed as the surface to be acid etched. All other surfaces of the rock sample are covered with an acid-resistant protective layer to achieve directional single-sided acid etching. Step S2, acid etching treatment: Place the coated rock sample in a reaction container so that the exposed end face comes into contact with the acid solution and carry out the acid etching reaction under the preset reservoir conditions. Step S3, filling and curing: Clean and dry the acid-etched rock sample (3), and use epoxy resin (4) to fill the acid-etched end face with vacuum negative pressure so that the epoxy resin completely fills the acid-etched pores (1) and microcracks formed by acid etching. After curing, a smooth rock-glue composite end face is formed. Step S4, Profile Preparation: Using the filled composite end face as a reference, the rock sample end face is polished layer by layer. After each polishing to a preset depth, polishing is performed to obtain a smooth test surface at different acid etching depths. Step S5, Micromechanical test: Micro-nano indentation technology is used to perform micro-nano indentation test 5 on the flat test surface at each depth to obtain the micromechanical parameters of the rock matrix (2) at the corresponding depth; Step S6, Damage Intensity Characterization: Using the micromechanical parameters of the undamaged rock matrix (2) as the benchmark, calculate the difference between the test value and the benchmark value at different acid etching depths, obtain the acid etching damage intensity at the corresponding depth, and establish a quantitative relationship between the evolution of acid etching damage intensity and acid etching depth.
2. The characterization method according to claim 1, characterized in that, In step S1, the rock sample (3) is a cylinder with only one end exposed as the surface to be acid-etched. The remaining surfaces, including the other bottom and side surfaces, are coated with acid-resistant material to form a protective layer. The acid-resistant protective layer is a polytetrafluoroethylene acid-resistant coating or an epoxy resin acid-resistant adhesive. Its acid resistance temperature is not lower than 150℃, its acid resistance pressure is not lower than 10MPa, and its protective layer thickness is 0.4-0.6mm.
3. The characterization method according to claim 1, characterized in that, In step S2, the reaction vessel is a high-temperature and high-pressure reactor. The reservoir operating conditions include acid concentration, reaction temperature, reaction pressure, reaction time, and pH value. During the reaction, the acid concentration is monitored in real time and acid is replenished, while stirring is performed to ensure uniform acid concentration. The parameters are controlled through the reaction vessel to simulate different reservoir conditions.
4. The characterization method according to claim 1, characterized in that, In step S3, the acid-etched rock sample (2) is rinsed with flowing deionized water and dried at 40-50℃. The vacuum negative pressure filling process is to first inject epoxy resin (4) to submerge the acid-etched end face, and then immediately put it into a sealed chamber to be vacuumed to -0.05--0.1MPa and pressure maintained to remove the gas in the pores to ensure that the epoxy resin penetrates the acid-etched pores (1) and microcracks. Ultrasonic vibration is used for 5-10 minutes to remove air bubbles, and then heat and pressure are maintained for 24 hours to complete the curing.
5. The characterization method according to claim 1, characterized in that, In step S4, the depth interval of the layer-by-layer grinding is 10μm-30μm, and the grinding depth covers the entire acid-affected layer to the undamaged bedrock layer; the test surface at each depth is polished to a finer grit than 1000 mesh through step-by-step grinding and polishing, so that its surface roughness Ra < 0.05μm.
6. The characterization method according to claim 1, characterized in that, In step S5, the micro-nano indentation test (5) uses a Berkovich diamond indenter with a loading load range of 0.1-500mN and an indentation depth range of 100-5000nm. At least 49 test points are arranged in a matrix on each test surface, and the test points are arranged in the rock matrix 2 area to avoid the epoxy resin filled area.
7. The characterization method according to claim 1, characterized in that, In step S5, if the indentation points cover the bonding area between the epoxy resin (4) and the rock matrix (2), the bearing area ratio of the rock matrix (2) and the epoxy resin (4) is calculated through microscopic observation. The mechanical parameters obtained from the test are then corrected by area weighting according to the following formula. After separating the microscopic mechanical parameters of the rock matrix (2), the acid etching strength loss value is calculated: ; in, The micromechanical parameters of the rock matrix (2) are given. These are the comprehensive mechanical parameters obtained from the indentation test; The percentage of the bearing area of epoxy resin (4) within the indentation range; The micromechanical parameters of pure epoxy resin (4) are given. The percentage of the bearing area of the rock matrix (2) within the indentation range.
8. The characterization method according to claim 1, characterized in that, In step S6, the acid etching intensity loss value is calculated using the following formula: ; in, For depth The acid etching intensity loss value at the location; The reference values for the micromechanical parameters of the undamaged rock matrix (2) are: For depth Test values of micromechanical parameters of rock matrix after acid etching.
9. The characterization method according to claim 1, characterized in that, In step S6, the reference value of the undamaged rock matrix (2) is taken from the test results of the un-acid-etched area of the same rock sample, or from the test results of the rock sample being ground to the deep undamaged layer; the micromechanical parameters include microhardness and / or elastic modulus.
10. The characterization method according to claim 1, characterized in that, In step S6, an exponential decay model is used to fit the relationship between acid etching depth and acid etching intensity loss value, and the resulting law of acid etching damage intensity evolution satisfies the following equation: ; in, This represents the loss of acid etching strength. This refers to the depth of acid etching. , , represents the fitting constant under the corresponding experimental conditions.